Itinerary of Race Discussions in Three Afro-Descendant Intellectuals from the Hispanic Caribbean - Oliva, Elena (Meridional. Revista Chilena de Estudios Latinoamericanos, 2018)
This article analyzes the discourse of three Afro-descendant intellectuals from the Hispanic Caribbean, whose work addresses racism as an ongoing discussion throughout the entire 20th century. To that end, it defines Afro-descendant intellectuals in terms of an analytical category and proposes a general periodization of their thought in Latin America, comprised of three crucial moments. The first moment corresponds to the first half of the 20th century and is characterized by a discussion that connects racism to national belonging. Gustavo Urrutia examines this relationship in Cuba, one of the most prolific countries for Afro-Latin American intellectual production. The second moment covers the sixties and seventies, when racism is articulated with the problem of imperialism, circumstances in which Isabelo Zenón’s reflections from Puerto Rican are representative, given the island’s political situation. The third moment spans from the eighties up to the present day and is associated to an identity shift toward diaspora and afro-descendants, the groundwork from which Afro-Latin American movements begin to spread beyond national boundaries. In this context, Dominican intellectual Ochy Curiel renews discussions of racism from an anti-racist feminist perspective